The presence of the risen Jesus in and among his followers with special reference to the first farewell discourse in John 13:31-14:31 - Van der Watt, J.G. (Jan Gabriel), 1952- (University of Pretoria, 2013)
Thesis (PhD (New Testament Studies))--University of Pretoria, 2007.